2023
DOI: 10.3390/ma16031075
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Wet Granulation on Tribological Behaviors of Cu-Based Friction Materials

Abstract: Because of the excellent thermal conduction, corrosion resistance, and tribological properties, copper-based friction materials (CBFMs) were widely used in airplanes, high-speed trains, and wind power generation. With operating speed continuously increasing, CBFMs are suffering more complicated and extreme working conditions, which would cause abnormal abrasion. This paper presents an experiment to investigate how the tribological behaviors of CBFMs are regulated by granulation technology. Samples were prepare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…As observed in Figure 11 a, a large amount of wear debris and pits were found, indicating that the wear mechanisms were severe abrasive wear and adhesive wear [ 5 ]. In fact, the composition of RBFMs can determine wear resistance and then influence its wear mechanisms [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As observed in Figure 11 a, a large amount of wear debris and pits were found, indicating that the wear mechanisms were severe abrasive wear and adhesive wear [ 5 ]. In fact, the composition of RBFMs can determine wear resistance and then influence its wear mechanisms [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…As an important part in brake systems, resin-based friction materials (RBFMs) are the last line of defense for safe operation; their stability and reliability are directly related to the safety of passengers [ 2 , 3 ]. At present, friction materials applied to brake systems can be divided into four categories: ceramic-based friction materials, resin-based friction materials, powder metallurgy friction materials, and C/C composite materials [ 4 , 5 , 6 ]. Among them, RBFMs are widely used because of their simple preparation and low cost [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Initially, phenol formaldehyde, barium sulfate, alumina powder, tire rubber, graphite and white ark shell powder were mixed in a mixer for 5 min. Thereafter, fibers were added and mixed homogeneously for another 20 min in a rotary ball milling machine with 10:1 ball to powder ratio to avoid the husk formation of fibers [36]. The prepared mix was added into a mold cavity and hot pressed at a temperature of 160 °C-170 °C and pressure of 12 MPa for 10 min.…”
Section: Specimens Preparationmentioning
confidence: 99%
“…On the other hand, it reduces dust pollution, purifies the production environment and facilitates shipment 11 . Li et al 12 used granulation and cold press sintering to prepare copper‐based friction materials with better wear resistance than ungranulated ones. The results of Liu et al showed that the sulfur granulation process is not only environmentally friendly, but also results in a uniform particle size distribution of the raw material 13 …”
Section: Introductionmentioning
confidence: 99%